Trace elements and minerals content in hair of children with epileptic seizures, who had perinatal damage of central nervous system. Clinico-laboratory correlations - Bednenko, Liliya; Tikhonova, Marina; Philiptsov, Vladimir (ScienceRise: Medical Science, 2017)
Aim of research. Identify the features of the content of trace elements and minerals in hair in children with epileptic seizures that have undergone perinatal pathology of the central nervous system. To determine the specificity of elemental status in patients whose seizures could be stopped, and in patients resistant to pharmacotherapy. Methods. Twenty children with epileptic seizures underwent perinatal pathology of the central nervous system, aged from 3 months to 8 years (an average of 3.04±2.9 years) were controlled. Population is divided into two groups: I group (10 people) - children with epileptic seizures, managed to be stopped. Group II (10 people) - children with epileptic seizures, resistant to therapy. The control group consisted of 10 practically healthy children of the corresponding sex and age. The content of 25 chemical elements: Al, As, Be, Cd, Hg, Li, Ni. Pb, Sn, B, V, I, Ca, Co, Cr, Cu, Fe, K, Mg, Mn, Na, P, Se, Si, Zn, μg / g was determined in hair by atomic-emission spectrometry with inductively coupled argon plasma and mass spectrometry. Results. The children with epileptic seizures showed a statistically significant increase in the content of Ca, Mg, Mn, Pb, a decrease in Sn concentration when comparing the content of elements in the group II and the control group (p <0.05). The increase in the concentration of the toxic element Pb in the group of seriously ill children with pharmacoresistant persisting epileptic seizures is 3.5 times higher than in the control group (p <0.05). The amount of Ca, Mg, Mn, Pb (ƿ from 0.42 to 0.67) in hair directly correlated (according to Spearman) with the severity of the condition and the propensity to resistance to therapy, in feedback - Sn (ƿ -0, 53). The largest number of direct average and strong links with the severity of clinical evidence and the character of structural changes in the brain was noted in Mg. Conclusions. The revealed changes in elemental status may indicate a possible pathogenetic mechanism in the development of clinical symptoms in the patients examined, the formation of pharmaco-resistance to therapy due to a disturbance of the metal-ligand homeostasis. More studies are needed to clarify the importance of the exchange of micro- and macroelements in the development of the disease